The very massive X-ray bright binary system Wack 2134 (= WR 21a) - Niemelä, Virpi Sinikka (2008)
From the radial velocities of the N IV λ4058 and He II λ4686 emission lines, and the N v λ4604-20 absorption lines, determined in digital spectra, we report the discovery that the X-ray bright emission line star Wack 2134 (= WR 21a) is a spectroscopic binary system with an orbital period of 31.673 ± 0.002 d. With this period, the N IV and He II emission and N v absorption lines, which originate in the atmosphere of the primary component, define a rather eccentric binary orbit (e = 0.64 ± 0.03). The radial velocity variations of the N v absorptions have a lower amplitude than those of the He II emission. Such a behaviour of the emission line radial velocities could be due to distortions produced by a superimposed absorption component from the companion. High-resolution echelle spectra observed during the quadrature phases of the binary show H and He II absorptions of both components with a radial velocity difference of about 541 km s-1. From this difference, we infer quite high values of the minimum masses, of about 87 and 53 M⊙ for the primary and secondary components, respectively, if the radial velocity variations of the He II emission represent the true orbit of the primary. No He i absorption lines are observed in our spectra. Thus, the secondary component in the Wack 2134 binary system appears to be an early O-type star. From the presence of H, He II and N v absorptions, and N IV and C IV emissions, in the spectrum of the primary component, it most clearly resembles those of Of/WNLha-type stars.